CT angiography for coronary graft assessment - Chartrand-Lefebvre, Carl; Stevens, Louis-Mathieu; Mansour, Samer; Noiseux, Nicolas (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
We read with interest the article “CT angio for the evaluation of graft patency” by Di Lazzaro and Crusco (1) in the April 2017 issue of the Journal of Thoracic Disease. The authors describe technological advances of modern computed tomography (CT) systems as well as the high accuracy for coronary artery bypass graft (CABG) assessment, making CT angiography a noninvasive alternative of choice to catheter coronary angiography in patients with CABG, in clinical settings as nicely reviewed by the authors, but also in the context of research protocols.